DESIGN OF ASSESSMENT SYSTEM FOR PNEUMATIC ARTIFICIAL MUSCLEâS PERFORMANCE INDICATORS AS A PART OF REHABILITATION GLOVES - Rehanda, Adfialdho
Recently, many people with temporary paralysis need rehabilitation or physiotherapy as a intervention to cure their paralysis. One of the most common cause in the degradation of someone’s ability in perfoming daily activities is paralysis in hand motor function. Even until now, physiotherapy is still performed by using conventional tools, especially here in Indonesia. Intervention with advanced technology can be hardly found in the clinical application. This is due to the high cost for the advanced tools, since it still relies heavily on mechatronics system. Nowadays, there are advanced systems which based their design on soft materials so they are able to compress the production cost of the tool. The soft material produces a tool called pneumatic artificial muscle (PAM) or soft-actuators. In this research, we design a regulated air pressure supply system for testing the performance indicators of PAM. There are several parameters that we can obtain from the test, they are linearity, sensitivity, time constant, and gain. From the test, we know that the system is linear in the range of 50-200 kPa with sensitivity of 0,0874 N/kPa. The time constant varies between 1,4877-4,9139 seconds for several combination of servo valve opening percentage and pressure supply value. Hand motion analysis is also performed by using computer vision to see the effect of the chosen combination of servo valve opening and pressure supply to the hand motion. It shows that every subject gives different result, based on how fast the PAM reaches the steady state condition. This can be caused by the difference in the physical condition and habits of the subject.